Role of Bala Taila Nasya and Rasnadi Guggulu in Karnasrava (Chronic Suppurative Otitis Media) (International Journal of Ayurveda and Pharma Research, 2022)
In Ayurveda, Karnasrava is mentioned as Vata Pradhan Tridoshaja and Sadhya Vyadhi in Shalakya Tantra. The term Karnasrava is self explainatory itself, which means Srava (discharge) from Karna (ear). For this study 30 patients were registered from OPD/IPD of Gurukul Campus, Haridwar; who were clinically diagnosed patients of Karnasrava/CSOM. There was only one group, so combined effect of Bala Taila Nasya and Rasnadi Guggulu was seen in patients. Results of the study indicates that highly significant result was seen in earache, Karnasrava (quantity of discharge), tenderness over mastoid antrum and consistency of discharge. Not significant result was seen in degree of hearing loss while in T.M. perforation size result was only significant.